Characteristics and influence on quality of life of new‐onset pain in critical COVID‐19 survivors. (15th December 2021) - Ojeda, Antonio; Calvo, Andrea; Cuñat, Tomas; Mellado‐Artigas, Ricard; Comino‐Trinidad, Oscar; Aliaga, Jorge; Arias, Marilyn; Ferrando, Carlos; Martinez‐Pallí, Graciela; Dürsteler, Christian
Abstract: Background: Pain is a clinical feature of COVID‐19, however, data about persistent pain after hospital discharge, especially among ICU survivors is scarce. The aim of this study was to explore the incidence and characteristics of new‐onset pain and its impact on Health‐Related Quality of Life (HRQoL), and to quantify the presence of mood disorders in critically ill COVID‐19 survivors. Methods: This is a preliminary report of PAIN‐COVID trial (NCT04394169) presenting a descriptive analysis in critically ill COVID‐19 survivors, following in person interview 1 month after hospital discharge. Pain was assessed using the Brief Pain Inventory, the Douleur Neuropathique 4 questionnaire and the Pain Catastrophizing Scale. HRQoL was evaluated with the EQ 5D/5L, and mood disorders with the Hospital Anxiety and Depression Scale (HADS). Results: From 27 May to 19 July 2020, 203 patients were consecutively screened for eligibility, and 65 were included in this analysis. Of these, 50.8% patients reported new‐onset pain; 38.5% clinically significant pain (numerical rating score ≥3 for average pain intensity); 16.9% neuropathic pain; 4.6% pain catastrophizing thoughts, 44.6% pain in ≥2 body sites and 7.7% widespread pain. Patients with new‐onset pain had a worse EQ‐VAS and EQ index value ( p < 0.001). Pain intensity was negatively correlated to both the former (Spearman ρ : −0.546, p < 0.001) and the latter (Spearman ρ : −0.387, p = 0.001). HADS anxiety and depression values equal or above eight were obtained in 10.8% and 7.7% of patients, respectively. Conclusion: New‐onset pain in critically ill COVID‐19 survivors is frequent, and it is associated with a lower HRQoL. Trial registration No.: NCT04394169. Registered 19 May 2020. https://clinicaltrials.gov/ct2/show/NCT04394169 . Significance: A substantial proportion of severe COVID‐19 survivors may develop clinically significant persistent pain, post‐intensive care syndrome and chronic ICU‐related pain. Given the number of infections worldwide and the unprecedented size of the population of critical illness survivors, providing information about the incidence of new‐onset pain, its characteristics, and its influence on the patients' quality of life might help establish and improve pain management strategies.